2018
DOI: 10.3390/cli6010006
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Model Projections of River Flood Risk in Europe under Global Warming

Abstract: Abstract:Knowledge on the costs of natural disasters under climate change is key information for planning adaptation and mitigation strategies of future climate policies. Impact models for large scale flood risk assessment have made leaps forward in the past few years, thanks to the increased availability of high resolution climate projections and of information on local exposure and vulnerability to river floods. Yet, state-of-the-art flood impact models rely on a number of input data and techniques that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 49 publications
(61 reference statements)
1
80
0
Order By: Relevance
“…Modeled asset damages in this study are validated in the study of Alfieri et al (2018), which shows that they are well in line with observed asset damages. More difficult is the validation of the modeled indirect losses (Koks 2018), which has proven to be difficult as the wider economic impacts after a disaster are not (well) documented and, for Europe, are lacking almost completely.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Modeled asset damages in this study are validated in the study of Alfieri et al (2018), which shows that they are well in line with observed asset damages. More difficult is the validation of the modeled indirect losses (Koks 2018), which has proven to be difficult as the wider economic impacts after a disaster are not (well) documented and, for Europe, are lacking almost completely.…”
Section: Discussionsupporting
confidence: 76%
“…In Europe, large-scale floods occur almost every year and, due to climate change, their frequency and magnitude is expected to increase (Kundzewicz et al 2014, Forzieri et al 2016, Alfieri et al 2018. Floods can affect several river basins or countries at the same time, leading to highly correlated direct damages (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The set of climate models were selected as representative of a range of outcomes for future climate change, including high and low climate sensitivity, different biases in baseline precipitation climatology, and different global patterns of precipitation change (Alfieri et al, 2017(Alfieri et al, , 2018. The set of climate models were selected as representative of a range of outcomes for future climate change, including high and low climate sensitivity, different biases in baseline precipitation climatology, and different global patterns of precipitation change (Alfieri et al, 2017(Alfieri et al, , 2018.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…We use an ensemble of high-resolution climate simulations from downscaled general circulation models under RCP 8.5 and analyze drought conditions over 30-year time windows centered on the SWLs. The set of climate models were selected as representative of a range of outcomes for future climate change, including high and low climate sensitivity, different biases in baseline precipitation climatology, and different global patterns of precipitation change (Alfieri et al, 2017(Alfieri et al, , 2018. Drought changes with respect to historical conditions are derived from a peak over threshold analysis using the SPEI multiscalar drought index that represents both the supply and demand sides of the surface moisture balance.…”
Section: Naumann Et Al 3285mentioning
confidence: 99%
“…global warming, precipitation, RCP4.5 and RCP8.5 scenarios, RegCM4, surface temperature 1 | INTRODUCTION Global warming and its impact on the water cycle have attracted a great attention of the scientific community in recent years (e.g., Trenberth et al, 2014;Alfieri et al, 2018). Many aspects of the water cycle have undergone changes in a warming climate, including more intense droughts in some areas (Trenberth et al, 2014) and more frequent floods in others (Alfieri et al, 2018). Reduction of precipitation in subtropical semi-arid to arid regions under global warming is noted in most previous studies (e.g., Alizadeh-Choobari and Najafi, 2018b), and this certainly has exacerbated semi-arid to arid conditions over these regions.…”
Section: Introductionmentioning
confidence: 99%